Adverse wind conditions during northward Sahara crossings increase the in‐flight mortality of Black‐tailed Godwits. (17th September 2019) - Loonstra, A. H. Jelle; Verhoeven, Mo A.; Senner, Nathan R.; Both, Christiaan; Piersma, Theunis
Abstract: Long‐distance migratory flights are predicted to be associated with higher mortality rates when individuals encounter adverse weather conditions. However, directly connecting environmental conditions experienced in‐flight with the survival of migrants has proven difficult. We studied how the in‐flight mortality of 53 satellite‐tagged Black‐tailed Godwits ( Limosa limosa limosa ) during 132 crossings of the Sahara Desert, a major geographical barrier along their migration route between The Netherlands and sub‐Saharan Africa, is correlated with the experienced wind conditions and departure date during both southward and northward migration. We show that godwits experienced higher wind assistance during southward crossings, which seems to reflect local prevailing trade winds. Critically, we found that fatal northward crossings (15 deaths during 61 crossings) were associated with adverse wind conditions. Wind conditions during migration can thus directly influence vital rates. Changing wind conditions associated with global change may thus profoundly influence the costs of long‐distance migration in the future. Abstract : Black‐tailed Godwits (Limosa limosa limosa) cross the Sahara Desert twice a year while migrating from their breeding grounds to the sub‐Saharan African wintering grounds. During southward Sahara crossings, godwits experience a higher wind assistance than during northward crossings. Critically, fatal northward crossings were associated with a low wind assistance. In‐flight experienced wind conditions can thus influence the probability to successfully cross a major geographic barrier. Photo: Jan van de Kam.